(untitled) - O'Connor, Flannery (New York, NY, 1988)
The included essays are O'Connors most well-known and provide important and interesting insights into her writing and themes. Many of the letters are intriguing, but many others consist of a few lines and are not extremely useful (there's a two-line letter to Walker Percy, congratulating him on an award, which tells us virtually nothing at all; include it in a book of O'Connor's letters but not in a sampling of her best and most important).
Keywords: American literature,American essays; 20th century,20th century